Effects of feeding Cashew Apple Waste with or without Supplementation of Non-starch Polysaccharide Degrading Enzymes on Nutrient Digestibility and Growth Performance of broilers - Venkatramana, P; S, Senthil Murugan; Chacko, Biju; S., Patki H.; K, Shyama; C, Sunanda (Indian Journal of Animal Nutrition, 2020)
The current research was carried out to study the effect of different inclusion level of cashew apple waste (CAW) to improve the ileal digestibility of nutrients and performance of broilers supplemented with non-starch polysaccharides (NSP) degrading enzymes. Two hundred and ten day-old Vencobb broiler chicks divided into 7 groups with 3 replicates of 10 chicks in each. Birds of groups G1, G2, G3 which received CAW at 0, 5 and 10 per cent, respectively. G4 and G5 birds fed with 5 per cent CAW, and were additionally fed NSP degrading enzyme at 500 g and 750 g/ton, respectively. Similarly, G6 and G7 birds received 10 per cent CAW, and NSP degrading enzyme at 500 and 750 g/ton, respectively. Ileal digestibility values of dry matter, crude protein and crude fibre were significantly (P<0.01) increased in enzyme supplemented group with CAW. Feed intake did not differ significantly (P<0.11) among the groups at 42nd day. Body weight Gain and feed conversion ratio recorded in experimental birds received 10 per cent CAW and NSP degrading enzyme at 750 g/ton was comparable to control group (G1). However, better feed conversion efficiency (P<0.01) was recorded G4 and G5 group birds compared to control (G1). Thus, CAW could be included in corn, soya bean meal based broiler ration at 10 % level with NSP enzyme at 75 0 g/ton.